Stroverwerkende afdeling van een glasfabriek. Kopie van exemplaar van Dir. Gen. van den Arbeid, Den Haag, nr. 32818
Stroverwerkende afdeling van een glasfabriek. Kopie van exemplaar van Dir. Gen. van den Arbeid, Den Haag, nr. 32818.